Patterns of teacher-child relationships quality: Young children’s perspectives - Anastasia Vatou; Athanasios Gregoriadis; Nikolaos Tsigilis; Vasilis Grammatikopoulos (Journal of Early Childhood Education Research, 2020)
Examining children’s perspectives about the quality of teacher-child relationships can contribute significantly to our understanding of how the quality of these relationships is developed. The Child Appraisal of the Relationship with the Teacher Scale (CARTS) is a newly developed measure that assesses the quality of teacher-child relationships from children’s perspectives. The purpose of this study was a) to confirm the factor structure of the Greek version of CARTS, b) to examine whether any patterns of teacher-child relationships exist, and c) if they are associated with children’s gender and age. The sample consisted of 365 preschool children from Greece. Results confirmed the construct validity of the CARTS scale. Consistent with attachment-based research, results revealed four types of teacher-child relationships. In addition, results showed that patterns of teacher-child relationships based on children’s perspectives, similar to those of teachers’ perspectives, are existent from the early years.